Pengembangan Aplikasi Pelatihan dan Manajemen Tim Bola Basket SABAC berbasis Web (Studi Kasus : SMAN 7 Malang) - Jati Nugroho; Agi Putra Kharisma; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Training is an activity which develops an ability in certain fields. Training is a major part of building a basketball team. But in a Basketball team there is also a need for management. Management itself is a principle in regulating, building or compiling a plan or an organization. Training on the SABAC Team, which still uses manual methods and the management of players who still cannot be organized, is certainly a problem for the coach and also the players. Likewise, the Extracurricular Superintendent and Principal who can only come to a training session once a month still cannot see the development of the players from the SABAC Team significantly. However, among these factors, the Covid-19 pandemic is the main factor that hinders all these activities until the government takes an action called Social Distancing which causes delays in training and also correspondence between trainers, extracurricular supervisors and also school principals related to activities or events that will be carried out by the SABAC Team. Based on the problems that have been described, an application is made that facilitates the training or management process during this pandemic. In its development this application was built using the waterfall method and also a web-based application was chosen because it can be used on various platforms. From the results of the needs analysis obtained from interviews and also direct observations to the field, it produces 5 main actors, 64 functional needs and 1 non-functional requirement. For the design part of the application, Sequence Diagrams, Class Diagrams, Entity Relationship Diagrams, pseudocode and database design are the main parts in the system development process. In the implementation process, the PHP language becomes the builder of the object-based system and MySQL becomes the data storage part of the system. The next process is the testing stage where there is white-box testing consisting of unit testing and integration testing and also black-box testing to test all the validity of all functionalities. And there is also a Compatibility test where the testing process is assisted by an application called SortSite which tests on several browsers and also on Android and IOS, the result of this test is that the application can run smoothly without any missing content or error functionality.